(untitled) (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2018)
هدفت الدراسة للتعرف إلى درجة استخدام مدرسي الحلقة الثانية من التعليم الأساسي لطرائق تنمية التفكير الإبداعي في تدريس الفيزياء بمحافظة اللاذقية، للفصل الأول من العام الدراسي (2010/2011م)، وقد تكون مجتمع الدراسة من جميع مدرسي مادة الفيزياء في الحلقة الثانية من التعليم الأساسي وعددهم (500)، وتكونت عينة الدراسة من (40) مدرساً ومدرسة، وقد أعدت الباحثة أداة الدراسة وهي بطاقة ملاحظة، وتم التحقق من صدق أداة الدراسة وثباتها، حيث بلغ معامل الثبات (0.89). وقد أظهرت نتائج الدراسة أن درجة استخدام مدرسي الفيزياء في الحلقة الثانية من التعليم الأساسي لأساليب تنمية التفكير الإبداعي كان بدرجة متوسطة بلغت (1.5)، كما أظهرت النتائج وجود فروق ذات دلالة إحصائية تابعة لمتغير الخبرة في التدريس، حيث كانت الفروق لصالح المدرسين الذين يمتلكون سنوات خبرة، أكثر من المدرسين الجدد في المهنة. The study aimed at identifying the extent to which teachers of the second Cycle in basic education use the creative thinking in teaching Physics in Lattakia governorate. The study was implemented during the first semester of the classes of (2010-2011). The research involved (500) teachers; (40) Male and Female teachers were chosen as a sample. The Instrument of the research was the Observation Card, with a reliability rate of (0.89) Means. Results were calculated using the following test: (t- test). The study revealed that the degree of using the creative thinking style by second circle essential education teachers of physics in Lattakia governorate is low with percentage (32.4%(. There were statistically significant differences related to the teacher’s experience. These differences were more to the advantage of teachers of long teaching experience than those new in the profession.